Realistic acoustic sensor network deployment and radio coverage in terrain profile using 3d modeling - Sharma, Gajendra; Kumar, Manish; Verma, Shekhar (International Journal of Engineering and Technology, 2018)
Acoustic sensing can be done by deploying a wireless sensor network in the area of interest. To detect anthrophonic events such as, deforestation along with monitoring the vehicle movement on the muddy road for smuggling intension. In the present time, anthrophonic event classification on the basis of wireless acoustic sensor node remain unanswered. This work explores speedy improvement in wireless acoustic sensor node that classify acoustic event applications. Wireless acoustic sensor node deployment strategy in outside surroundings is proposed. Most of the studies on sensor network in term of deployment consider on flat surfaces. The deployment of wireless sensor network in unequal surface like a forest was rarely reported. The aim is to maximize the quality of coverage of a wireless sensor on a forest surface. A probabilistic sensing model and line of sight algorithm are utilized for this purpose.